UPAYA MENINGKATKAN HASIL BELAJAR PPKN DENGAN MODEL PROBLEM BASED LEARNING PADA SISWA KELAS IV SDN PULOGEBANG 07 JAKARTA TIMUR - Putri, Nevika Sitara; Nurul, Talha Jasmine; Muji Utami, Nidya Chandra; Taofik, Taofik (Dharmas Education Journal (DE_Journal), 2023)
This study seeks to enhance PPKn learning outcomes by implementing the PBL (Problem-Based Learning) paradigm with students in grade four at SDN Pulo Gebang 07. This study employed classroom action research on a sample of 26 fourth-grade students. Testing, observation, and documentation are methods for collecting data. This study's findings support the claim that PBL improves academic outcomes for students. The outcomes of Cycle I demonstrate this, where 12 students completed the course (46.15%) and 14 students did not (53.84%). The second cycle of students who completed was 23 students (88.46%), while 3 students were incomplete (11.53%).